2015
DOI: 10.1049/iet-ifs.2014.0183
|View full text |Cite
|
Sign up to set email alerts
|

Impossible differential cryptanalysis of MARS‐like structures

Abstract: The MARS-like structure is a generalised Feistel structure. Unified impossible differential (UID) method is an effective method to discover impossible differential characteristics for block cipher structures. In this study, for a specific kind of MARS-like structure, the authors use UID to show that when n, the number of subblocks, is even, there always exist 3n − 1 rounds impossible differentials. Moreover, the authors prove that when n is odd, the MARS-like structure has impossible differentials for any numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Using the UID method [19], Xue and Lai constructed false(3n1false) ‐round impossible differentials of MARS‐like structures as long as the round function is bijective. In this section, we are going to prove the existence of 3 n ‐round impossible differentials when the bijective round function is SP‐type.…”
Section: Impossible Differentials Of Mars‐like Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the UID method [19], Xue and Lai constructed false(3n1false) ‐round impossible differentials of MARS‐like structures as long as the round function is bijective. In this section, we are going to prove the existence of 3 n ‐round impossible differentials when the bijective round function is SP‐type.…”
Section: Impossible Differentials Of Mars‐like Structuresmentioning
confidence: 99%
“…considered the case when the round function is not bijective and showed that there exist 2 n ‐round impossible differentials of MARS‐like structures with n subblocks [18]. In 2015, Xue and Lai [19] constructed false(3n1false) ‐round impossible differentials of MARS‐like structures in the setting where the round function is bijective, and they also presented a trivial result about the MARS‐like structure when the subblock number n is odd. The impossible differential properties of Feistel ciphers with SP round function is studied by Wei et al .…”
Section: Introductionmentioning
confidence: 99%
“…For m-dataline MARS-like structure, when the round function is any bijective transformation, (2m − 1)-round impossible differentials were presented by the U method in [13]. is result was improved to (3m − 1) rounds in [19]. Furthermore, when the round function takes SP type, 3m-round impossible differentials were found in [5].…”
Section: Introductionmentioning
confidence: 99%
“…(3) For m-dataline MARS-like structure, when the round function takes SPS type (namely, MARS SPS ), the previous best result of MARS SPS was also presented in [19]. ey showed that (3m − 1)-round impossible differentials were constructed with P satisfying the bijective condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation